Bibliometric Analysis of the Influence of Academic Research on HRM Strategy, Employee Performance, and Organizational Success Globally - Muhammad Syafri; Ahmad Muktamar; Achmad Choerudin; Roosganda Elizabeth; Mei Rani Amalia (Eastasouth Institute, 2023)
This bibliometric analysis explores the profound influence of academic research on Human Resource Management (HRM) strategy, employee performance, and global organizational success. Leveraging a comprehensive dataset from reputable academic databases, the study employs bibliometric techniques to analyze patterns of publication, citation, collaboration, and keyword trends within the HRM research domain. The findings reveal a multifaceted landscape of HRM scholarship. Co-authorship network analysis identifies prolific authors and research clusters, highlighting the collaborative nature of HRM research. Citation analysis uncovers highly influential publications, showcasing the impact of seminal works on HRM theory and practice. Keyword analysis unveils emerging research themes, reflecting the field's responsiveness to evolving challenges and trends. Notably, the analysis underscores the significance of evidence-based HRM practices and the global context in which HRM operates. It recognizes the role of academic research in shaping HRM strategies that enhance employee performance and contribute to global organizational success. This study provides valuable insights for HRM practitioners, researchers, and organizational leaders by offering a comprehensive overview of the evolving HRM landscape. It emphasizes the importance of collaboration, the influence of seminal works, and the dynamic nature of HRM research. Understanding these dynamics is pivotal for advancing HRM scholarship and driving organizational excellence in a globalized world.